2017
DOI: 10.1007/s10695-017-0404-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of lycopene against carbofuran toxicity in African catfish, Clarias gariepinus

Abstract: In the current study, African catfish, Clarias gariepinus, was exposed to a sublethal concentration of carbofuran (CF) to investigate its negative effects on biochemical and oxidative stress biomarkers. Also, the putative role of lycopene (LYC) administration in alleviating these negative effects was evaluated. Fish were divided into six groups in triplicates as follows: group I was without treatment, group II was orally administered corn oil, group III was orally administered 18 mg LYC/kg body weight, group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 69 publications
3
9
0
1
Order By: Relevance
“…African catfish were exposed to 0.121 mg CF L −1 and fed lycopene at a level of 18 mg and 9 mg per kg body weight for 1 month (Hamed & Osman, 2017). The results revealed that fish fed on 18 mg lycopene per kg body weight showed a pronounced alleviation of oxidative stress induced by CF via boosting the activities of CAT and SOD and reducing the MDA, GSH and TAC levels.…”
Section: The Role Of Lycopene In Reducing the Impacts Of Aquatic Envimentioning
confidence: 99%
See 1 more Smart Citation
“…African catfish were exposed to 0.121 mg CF L −1 and fed lycopene at a level of 18 mg and 9 mg per kg body weight for 1 month (Hamed & Osman, 2017). The results revealed that fish fed on 18 mg lycopene per kg body weight showed a pronounced alleviation of oxidative stress induced by CF via boosting the activities of CAT and SOD and reducing the MDA, GSH and TAC levels.…”
Section: The Role Of Lycopene In Reducing the Impacts Of Aquatic Envimentioning
confidence: 99%
“…It can alleviate the oxidative stress resulted from exposure of fish to sublethal levels of cadmium chloride (Mekkawy et al, 2011; Mekkawy et al, 2012), diazinon (DZN) (Ibrahim & Banaee, 2014; Ibrahim, 2015), zinc oxide nanoparticles (ZnONPs) (Abdel‐Daim et al, 2019), and endosulfan toxicity (Hussein et al, 2019). Lycopene also improved the hepatorenal functions and the haematological picture and reduced the serum oxidative stress biomarkers in African catfish ( Clarias gariepinus ) exposed to lead nitrate toxicity (Mahmoud et al, 2013), sublethal doses of atrazine (Mekkawy et al, 2013) and carbofuran (CF) (Hamed & Osman, 2017). Lycopene attenuates the oxidative stress responses and haemato‐immunological alterations of common carp ( Cyprinus carpio ) exposed to deltamethrin (DLM) (Yonar & Sakin, 2011), chlorpyrifos (CPF) (Ural, 2013), cypermethrin (CYP) (Yonar, 2013a), malathion (Yonar, 2013b) and trichlorfon (Yonar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that plants having medicinal properties can be used for mitigating metal toxicity (Abdel-Tawwab & Hamed, 2020;Hamed & Abdel-Tawwab, 2021). Similar studies also revealed that several plant-derived or chitosan-derived nanocomposite application in fish culture could enhance the survivability and safeguard from several water pollutants such as heavy metals, carbofuran Hamed & Osman, 2017), bisphenol-A (Hamed & Abdel-Tawwab, 2017;Hussein et al, 2021), ochratoxin-A (Abdel-Wahhab et al, 2016), etc.…”
Section: Discussionmentioning
confidence: 95%
“…AST and ALT are primarily liver enzymes associated with the metabolism of protein and amino acids. An elevated level of these enzymes in serum indicates liver damage (Hamed & Osman, 2017).…”
Section: Accumulation Of Heavy Metals Can Cause the Generation Of Reactivementioning
confidence: 99%
“…2). Следует указать, что в экспериментальных условиях, при кратковременных токсических нагрузках на рыб, другие исследователи наблюдали противоположный эффект [Hamed, Osman, 2017]. Для бухты Балаклавской повышенные величины изученных биохимических маркеров объясняются отличным от других акваторий рационом скорпены [Papoutsoglou, Papaparaskeva-Papoutsoglou, 1979].…”
Section: результаты и обсуждениеunclassified